2018
DOI: 10.1108/ara-01-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

A study of the relationships among environmental performance, environmental disclosure, and financial performance

Abstract: Purpose The purpose of this paper is to study the relationships among environmental performance (EP), environmental disclosure (ED), and financial performance (FP) (three corporate constructs) using data from Newsweek’s green rankings. Design/methodology/approach Previous studies document mixed results about the relations among the three constructs. A firm’s overall management strategy may affect the three constructs simultaneously; therefore, the interrelationships among EP, ED, and FP were jointly examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 49 publications
4
63
0
8
Order By: Relevance
“…Some researchers take only the presence of CER into account, for example, whether firms participate in the GRI reporting scheme or respond to the Carbon Disclosure Project (CDP) (e.g., Dawkins & Fraas, 2011a, 2011bLu & Taylor, 2018). A few others consider the completeness of disclosure, for example, the proportion of reported items in a reporting standard (e.g., Deswanto & Siregar, 2018;Hassan & Romilly, 2018).…”
Section: Reporting Aspectmentioning
confidence: 99%
“…Some researchers take only the presence of CER into account, for example, whether firms participate in the GRI reporting scheme or respond to the Carbon Disclosure Project (CDP) (e.g., Dawkins & Fraas, 2011a, 2011bLu & Taylor, 2018). A few others consider the completeness of disclosure, for example, the proportion of reported items in a reporting standard (e.g., Deswanto & Siregar, 2018;Hassan & Romilly, 2018).…”
Section: Reporting Aspectmentioning
confidence: 99%
“…For example, first, research which examines the effect of profitability on environmental disclosure. Deswanto & Siregar (2018), Lu & Taylor (2018) proved that the level of profitability does not affect environmental disclosure, whereas Chandok & Singh (2017) and Yanto & Muzzammil (2016) found that profitability has a negative effect on environmental disclosure. On the other hand, research conducted by Ismail et al (2018) found that profitability has a positive effect on environmental disclosure.…”
Section: Introductionmentioning
confidence: 98%
“…Legitimacy theory assumes that companies operate according to the norms and expectations of the surrounding community so that their existence is legally accepted (Lu & Taylor, 2018). Elkington (1997) also revealed the triple bottom line concept which focuses on economic prosperity, environmental quality, and social justice which is often called 3P namely profit, planet, and people.…”
Section: Introductionmentioning
confidence: 99%
“…Ismail et al(2018) defined environmental performance as an environmental certification that shows interest and willingness of a company to improve environmental quality. The selection of environmental performance as a moderating variable because according to Lu & Taylor (2018) companies that have good environmental performance will send a signal to the public to get praise and not harm stakeholders. Companies that have good environmental performance will be a driving force to be disclosed to the public that the companies have good environmental policy.…”
Section: Introductionmentioning
confidence: 99%
“…Legitimacy theory explains that in order to achieve legitimacy, companies need to work according to the norms and expectations of the community where they stand. A good environmental performance will be a positive signal to the community and prove that their activities do not harm the stakeholders (Lu & Taylor, 2018). Earnings management will have a negative impact on the company's image.…”
Section: Introductionmentioning
confidence: 99%